You are on page 1of 23

116 Problems in Algebra

Problems’ Proposer: Mohammad Jafari November 25, 2011

116 Problems in Algebra is a nice work of Mohammad Jafari. Tese problems have been published in a book, but it is in Persian (Farsi). Problems are very nice, so I 1 decided to collect a set of solutions for them. I should thank pco , socrates , applepi2000 , Potla, goldeneagle , and professordad who solved the problems and posted the solutions 2 .

Remark. A very few number of problems remained unsolved on AoPS. I will add the solutions of those problems as soon as I ﬁnd the book wr itten by Mr. Jafari. As this happened, problems’ numbers are not the same as the ﬁle posted on AoPS by the author 3 : they are consecutive.

User momed66 in AoPS website

1 Amir Hossein Parvardi

2 Topic in AoPS: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=444651

3 Topic in AoPS: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=406530

1

1 FUNCTIONAL EQUATIONS

2

1 Functional Equations

1. Find all functions f (x) from R R that satisfy:

f (x + y ) = f (x)f (y ) + xy

Solution. [First Solution] [by pco 4 ] Let P (x, y ) be the assertion f (x + y ) =

f (x)f (y ) +

then a such that f (a )

=

xy . Let f (1) = u . Tthe

0 : P (a, 0)

function f (x) = 0 x is not a Solution. Let

f (a )(f (0) 1) = 0 and so f (0) = 1.

f (1) = 2

u

=

u =

2

u (u 2 + 1) 2

=

=

f (1)f (1) = 2 =

P (1 , 1)

P (1 , 1)

=

=

f (2) = u 2 + 1

P (1 , 2)

=

f (1) = f (1)f (2) 2

u 2 2 u + 2 = 0, impossible

And so no solution.

Solution. [Second Solution] [by applepi2000] Let P (x, y ) be the above assertion.

Then:

P (0 , y ) =f (y ) = f (0)f

(y ).

So, either f (y ) is always 0, which isn’t a solution (test x = y = 1), or f (0) = 1.

Thus f (0) = 1 and:

Let x = 2 a . Then:

P (x, x) =f (x)f (x) x 2 =

1 .

1 + 4 a 2 = f (2 a )f (2 a ) =

(f (a ) 2 + a 2 )(f (a ) 2 + a 2 ) a 4 .

However, taking large a , such as a = 42, this is false. So, no such function

exists.

4 Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378997

 1 FUNCTIONAL EQUATIONS 3 2 Find all functions f (x) from R \ { 1 } → R such that: f (xy ) = f (x)f (y ) + xy

x, y R \ { 1 } .

Solution. [by pco] According to me, domain of functional equation must also

contain xy = 1.

Let then g (x) = f ( x ) deﬁned from (1 , + ) R .

x

The equation becomes P (x, y ) : g (xy ) = g (x)g (y ) + 1.

Let

Let then m = inf x> 1 g (x) and a n a sequence of reals in (1 , + ) such that

x > 1 : P ( x, x ) =g (x) = g ( x ) 2 + 1 1.

lim n+ g (a n ) = m .

P ( a n , a n ) =g (a n ) = g ( a n ) 2 + 1 m 2 + 1.

Setting n + in this inequality, we get m m 2 + 1, impossible. So no

solution.

3. Find all functions f : Z Z such that:

f (x) = 2 f (f (x)) x Z.

Solution. [by Rust and mavropnevma 5 ] From f (x) = 2 f (f (x)) we get 2 | f (x).

But then 2 | f (f (x)), so 4

this, we have 2 n | f (x) for

8 | f (x). Repeating

| f (x). But then 4 |

f (f (x)), so

all n N , so f (x) 0.

4. Find all functions f : Z Z and g : Z Z such that:

f (x) = 3 f (g (x)) x Z.

Solution. [by tkrass 6 ] f (g (x)) Z, so 3 |f (x) for all x

and 9 |f (x) for all x. By easy induction we get that f (x) is divisible by any power

Hence 3 |f (g (x))

Z.

of 3, hence f (x) 0. And g (x) may be any function taking integer values.

5 Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378363

6 Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378998

 1 FUNCTIONAL EQUATIONS 4 5 Find all functions f : Z → Z such that:

7 f (x) = 3 f (f (x)) + 2 x x Z.

Solution. [by Sansa 7 ] Let f (x) = g (x)+ 2 x, substituting in the main equation we get:

7(g (x) + 2 x) = 3 f (g (x) + 2 x) + 2 x =

7 g (x) + 12 x = 3(g (g (x) + 2 x) + 2 g (x) + 4 x) =

g (x) = 3 g (g (x) + 2 x)

Now let t (x) = g (x)+ 2 x, so we have: g (x) = 3 g (t (x)) At ﬁrst we found out that

3 |g (x) =3 |g (t (x)) =9 |g (x) · · · . Thus 3 n | f (x) = 2 x x R .

g (x) n N , so g (x) 0 =

6. Find all functions f : Q Q that for all x, y Q satisfy:

f (x

+ y + f (x + y )) = 2 f (x) + 2 f (y ).

Solution. [by socrates] Put y := 0 to get

f (x + f (x)) = 2 f (x) + 2 f (0).

Now, put x := x + y into the last equality to get

f (x + y + f (x + y )) = 2 f (x + y ) + 2 f (0).

This, together with the initial, gives

f (x + y ) f (0) = f (x) f (0) + f (y ) f (0),

so f (x) = ax + b. Substituting into the original equation, we ﬁnd the solutions:

7 Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378999

1 FUNCTIONAL EQUATIONS

f (x)

f (x) = 2 x, x.

= x,

x

7. Let f : R R be a function that for all x, y R satisﬁes:

f (x + f (x) + y ) = x Prove that f is a bijective function.

+ f (x) + 2 f (y ).

5

 Solution. [by socrates] Let P (x, y ) : f (x + f (x) + y ) = x + f (x) + 2 f (y ). Consider a, b such that f (a ) = f (b ). Then P (a, b ), P (b, a ) give a = b. So f is injective. Putting y := − f (x) we get

so f is clearly surjective.

f (f (x)) = x

2 ,

Actually, no such function exists: Put y := 0 , x := f (0) so, since f (f (0)) =

0 , f (0) = 0 . So x := 0 gives f 0 which is not a solution .

8. Find all functions f : R R such that for all real x, y we have:

f (x + f (x) + 2 y ) = x + f (f (x)) + 2 f (y ).

Solution. [by applepi2000] Let P (x, y ) be the above assertion, let a be an

arbitrary real number. Then:

P (2 a, a ) =f (a ) = a.

We’re done!

9. Given a function f : R R such that:

f (x

+ f (x) + 2 y ) = x + f (x) + 2 f (y ).

1 FUNCTIONAL EQUATIONS

6

Solution. [by applepi2000] Let P (x, y ) be the above assertion.

P (x, f (x) ) =⇒ − x =

2

2

f (f (x) ).

2

So f is surjective. Now assume f (a ) = f (b ),

a = b and thus f is injective.

f

then from above a

2

b , so

2

=

Finally, let f (0) = n . Then from the above,

(n ) = 0 =f (0) = n . So n = 0 and f (0) = 0 as desired.

2

4

10. Find all functions f : R + R + such that for all x > y > 0 we have:

1

f (x y ) = f (x) f (x)f ( x )y.

Solution. [by Dijkschneier 8 ]

1

P (x, y ) : f (x y ) = f (x) f (x)f ( x )y

f (x y ) > 0 =f (x)(1 yf ( x )) > 0

y x =x f (

=x f (x)x > 0

1 > y > 0 , P (1 , y ) =f (1 y ) = f (1) f (1) 2 y

Now take in particular 1 > y >

1 y f (1) f (1) 2 y

1 f (1) y (1 f (1))(1 + f (1))

(1 f (1))(1 y (1 + f (1))) 0

So f (1 y ) = 1 y , and hence f (y ) = y 1 > y > 0.

For 0 < x < 1, we have x = f (x) and so from the inequality

1

=

y

> f (

x )

1

1

1

1

x )

1

(1+ f (1)) and so:

=

=

=

=

=

f (1)

1

f (1) = 1

1

x y f (x y ) = f (x) f (x)f ( x )y

=x f (x)

y (1 f (x)f (1 /x))

1

x =

1

f ( x )

1

f ( x ) x , that is, f ( x ) = x 1 .

1

1

8 Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=424694

1 FUNCTIONAL EQUATIONS

Hence f (x) = xx > 1 and so in conclusion:

conversely is a solution.

7

f (x) = xx > 0, which

11. Find all functions f : R R such that

for all x, y R .

f (f (x + f (y ))) = x + f (y ) + f (x +

y ),

+ f (y ))) = x + f (y ) +

f (x + y ) If f (a ) = f (b ) for some a, b , then, comparing P (x b, a ) and P (x b, b ), we get f (x) = f (x + a b ) x But then, comparing P (x, y ) and P (x + a b, y ), we get x = x + a b and so a = b and f (x) is injective.

Solution. [by pco] Let P (x, y ) be the assertion f (f (x

P (f (x), x)

=

f (f (0))) = f (x f (x)) and so, since injective : f (0) =

x f (x) and f (x) = x + a , which

is never a solution.

So no solution.

12. Find all functions f : R + ∪ { 0 } → R + ∪ { 0 } such that

for all x, y R + ∪ { 0 } .

f (f (x +

f (y ))) = 2 x + f (x + y ),

Solution.

If f (a ) = f (b ) for some a, b , then, comparing P (x, a ) and P (x, b ), we get

f (x + a ) = f (x + b ) x But then, comparing P (x + a, y ) and P (x + b, y ), we get a = b and so f (x) is injective.

[by pco] Let P (x, y ) be the assertion f (f (x + f (y ))) = 2 x + f (x + y )

P (0 , x) =f (f (f (x))) = f (x) and,

So P (x, 0) becomes x + f (0) = 2 x +

since injective, f (f (x)) = x f (x) and so f (x) = f (0) x which is

never a Solution 1. (since < 0 for x great enough)

 1 FUNCTIONAL EQUATIONS 8 So no solution. 13. Find all functions f : R → R such that for all x, y ∈ R :

f (x + f (x) +

2 f (y )) = x + f (x) + y + f (y ).

Solution. [by socrates] Putting x := 0 we see that f is injective. Put x :=

y, y := x to get

f (x + f (x) + 2 f (y )) = x +

f (x) + y + f (y ) =

f (y + f (y ) + 2 f (x)),

so x + f (x)+ 2 f (y ) = y + f (y )+ 2 f (x) =f (x) x = f (y ) y, that is f (x) x

is constant: f (x) = x + c.

Substituing, we ﬁnd

f (x) = x, x.

14. Find all functions f : R R such that for all x, y R :

f (2 x + 2 f (y )) = x + f (x) + y + f (y ).

Solution. [by socrates] As in the previous problem,

f (2 y + 2 f (x)) so f (x) =

we get f (2 x + 2 f (y )) =

x + c. Substituing, we ﬁnd f (x) = x, x.

15. Find all functions f : R R such that for all x, y R satisfy:

f (f (x) + 2 f (y )) = f (x) + y + f (y ).

Solution. [by socrates] Putting x := 0 we see that f is injective. Put y := f (x)

to ﬁnd f (f (x)) = f (x). So,

is

x := f (y ) gives f (f (y )) = y and so f is

surjective. Finally, put y := 0 to get f (f (x) + 2 f (0)) = f (x) + f (0). Since f

surjective we get f (x) = x + c. Substituing, we ﬁnd f (x) = x, x.

16. Find all functions f

all x, y R f (x) + f (x) = 0 for all x R + The number of the elements of the set { x R |f (x) = 0 } is ﬁnite.

+ f (y )) = f 2 (x) + f (y ) for

:

R R such that f (x 2

1 FUNCTIONAL EQUATIONS

9

Solution. [by socrates] Assume f (x) > x for each x = 0 . Then 0 = f (x) +

 f (− x) > x − x = 0 contradiction. So f (a ) ≤ a for some a = 0 . Put x := a − f (a ), y := a into the ﬁrst condtion to get f (a ) = f 2 ( a − f (a ))+ f (a ) =⇒ f ( a − f (a )) = 0 , so f (c ) = 0 for some c. Now put x, y := c and we get f (c 2 ) = 0 and by induction f (c 2 n ) = 0 . If c = 0 , 1 , − 1 then Observe that third condition is false. So c = 0 , 1 , − 1 . if f (k ) > k (f (k ) < k ) then f (− k ) < − k (f (− k ) > − k ) so for

each x = 0 we have f (x) = x, x + 1 , x 1 . If f (l ) = l 1 for some l (the case f (l ) = l + 1 reduses to f (l ) = l 1)

then f (1) = 0 . So

f (1 + f (y )) = f (y ).

 • If f (2) = 2 then f (3) = 2 and so f (9) = f 2 (3) = 4 , impossible. • If f (2) = 1 then f (4) = f 2 (2) = 1, impossible. • f (2) = If 3 then f (4) = 9 , impossible.

Thus, f (x) = x, x = 0 . Finally, x := 0 gives f (0) = 0 so the only solution

is f (x) = x.

17. Let f : R R be an injective function that for all x, y R satisﬁes:

f (x + f (x)) = 2 x.

Prove that f (x) + x is a bijective function.

Solution. [by socrates] Let x + f (x) = g (x). So f (g (x)) = 2 x. g is clearly injective. Take y R , arbitrary and let f (y ) = 2 z = f (g (z )) so by injectivity of f we get g (z ) = y. We’re done.

18. Find all functions f : R R such that :

f (x + f (x) +

2 f (y )) = 2 x + y + f (y ) x, y R .

Solution. [by mousavi 9 ] It is obvious that f is injective.

9 Here: http://www.artofproblemsolving.com/Forum/viewtopic.php?t=378130

1 FUNCTIONAL EQUATIONS

10

 • x = y = 0 =⇒ f (3 f (0)) = f (0) =⇒ f (0) = 0 • y = 0 =⇒ f (x + f (x)) = 2 x • x = 0 =⇒ f (2 f (y )) = y + f (y ) =⇒ ff (2 f (y )) = 2 y
 Put f (2 f (y )) instead of y =⇒ f (x + f (x) + 4 y ) = 2 x + f (2 f (y )) + 2 y • x = 0 =⇒ f (4 y ) = 2 y + f (2 f (y )) • f (f (4 y ) − 2 y ) = 2 y + f (y + f (y )) • f (4 y ) − f (y ) = 3 y • y = − 2 x =⇒ f (x + f (x) + 2 f (− 2 x)) = f (− 2 x) • + 2 f (− 2 x) = 0 3 x + f (x) =⇒ − 6 x • + f (− 2 x) + 2 f (4 x) = 0 • 2 f (x) = − f (− 2 x) • x = − 2 x, y = x =⇒ f (− 2 x + f (− 2 x) + 2 f (x)) = − 4 x + x + f (x)

f (2 x) = 3 x + f (x)

2 f (x) = 3 x + f (x)

 • =⇒ f (x) = x. 19. Let f, g, h : R → R be functions such that f is injective and h is bijective,

satisfying f (g (x)) = h (x) for all x R . Prove that g is a bijective function.

Solution. [by socrates] Injectivity is obvious. Now take y R , arbitrary. There

 exists z : h (z ) = f (y ) = f (g (z )) so by injectivity of f we get g (z ) = y. We are done.

20. Find all functions f : R R such that for all x, y R satisfy:

f (2 x +

2 f (y )) = x + f (x) + 2 y.

Solution. [by socrates] Putting x := 0 we see that f is bijective. We have

 f (2 f (0)) = f (0) so f (0) = 0 . Put y := 0 to get f (2 x) = x + f (x). So the initial equation becomes f (2 x + 2 f (y )) = f (2 x) + f (2 f (y )) or f (x + y ) = f (x) + f (y )

from the surjectivity of f.

 1 FUNCTIONAL EQUATIONS 11 So, x + f (x) = f (2 x) = 2 f (x) =⇒ f (x) = x which is indeed a Solution 1. 21. Find all functions f : R + ∪ { 0 } → R + such that for all x, y ∈ R + ∪ { 0 } :

f ( x + f (x)

2

Solution. [by socrates] Put

+

y ) = f (x) + y.

y := y

+ f (y )

2

to get

So

f ( x + f (x) + y + f (y )

2

2

)

= f (x) + y + f (y )

2

.

f (y ) + x + f (x) = f ( x + f (x) + y + f (y )

2

2

2

) = f (x) +

y

+ f (y )

2

so f (x) x = f (y ) y, that is f (x) x is constant: f (x) = x + c. Substituing,

we ﬁnd f (x) = x, x.

22. Find all functions f : R + ∪ { 0 } →

R + ∪ { 0 } such that for

f ( x + f (x)

2

+ f (y )) = f (x) + y.

all x, y R + ∪ { 0 } :

Solution. [by socrates] Put x = y := 0 =f ( 3f (0) ) = f (0). Put x := 0 , y :=

2

3f (0)

2

:

f ( 3f (0) ) = 5f (0)

2

2

so f (0) = 0 .

respectively.

The former implies that f is injective and the latter f (x) = x, which is indeed

a Solution 1.

Now, x := 0 and y := 0 give f (f (y )) = y and f ( x + f ( x ) ) = f (x),

2

be a function such that f (x + y ) = f (x) + f (y ) for

all x, y R + ∪ { 0 } • The number of the elements of the set { x|f (x) = 0 , x R + ∪ { 0 }} is ﬁnite. Prove that f is injective function.

23. Let f : R + ∪ { 0 } → R

1 FUNCTIONAL EQUATIONS

12

Solution. [by socrates] We easily ﬁnd f (0) = 0 . Suppose there exist a, b 0

such that a = b and f (a ) = f (b ). Wlog assume a > b. Then f (a ) = f (a b + b ) =

f (a b ) + f (b ) so f (c ) = 0 for some c = 0 . So, by induction, f (2 n c ) = 0 for each

n N , contradicting the second condtion. So f is injective.

24. Find all functions f : R + ∪ { 0 } → R such that i) f (x + f (x) + 2 y ) =

f (2 x) + 2 f (y ), for all x, y R + ∪ { 0 } ii) The number of the elements of the set { x|f (x) = 0 , x R + ∪ { 0 }} is ﬁnite.

Solution. [by goldeneagle 10 Let P (a, b ) be the assertion. Let A be the set

which mentioned in the second condition. Deﬁne k = M ax(A).

2

If x > f (x) then P (x, x f ( x )

2

)

f ( x f ( x )

2

) = 0 f (x) x k so x

R + ∪ { 0 } : f (x) x k

I want to prove that

t = b a .

(I).

f is injective. If not, then a < b :

f (a ) = f (b ). Deﬁne

P

P ( a , x ), P ( , x ), (I) a + f ( a ) = b + f ( ) (II)

2

2

b

2

2

2

2

2

b

2

b

P (a, ), P (b, a ), (II)

2

2

f (2 a ) f (2 b ) = t (III)

(a, x), P (b, x), (III) ⇒ ∀x a + f (a ): f (x) f (x + t ) = t . But f (x) x k ,

so this is contradiction! (t > 0)

Now I want to prove that f (0) = 0. Deﬁne c = f (0). If c < 0, then

(0 , c ) f () = 0 and since f is injective we should have c = 0, contra-

P

diction!

2

c

2

So c 0. We have

P (0 , 0) f (c ) = 3 c

 • P (0 , x) ⇒ f (2 x + c ) = 2 f (x) + c (*) • P (c, x) ⇒ f (2 x + 4 c ) = 2 f (x) + f (2 c ) (**)

(*), (**) f (2 x + 4 c ) f (2 x + c ) = f (2 c ) c (x = c )f (5 c ) =

2

Put x = 2 c in (*): f (5 c ) = 2 f (2 c )+ c , so c = 0 and then P (x, 0)

2 f (2 c ) c

f (x) = x.

10 http://www.artofproblemsolving.com/Forum/viewtopic.php?t=442600

 1 FUNCTIONAL EQUATIONS 13 25 Find all functions f : R → R such that: • f (f (x) + y ) = x + f (y ) for all

x, y R for each x R + there exists some

y R + such that f (y ) = x.

Solution. [by socrates] Put y := 0 to

bijective. So, since f (f (0)) = f (0) we

get f (f (x)) = x + f (0) that is f is

0 . So f (f (x)) = x and

have f (0) =

 f (x + y ) = f (x) + f (y ). Since f bijective, for each x > 0 there exists unique y = f (x) such that f (y ) = x, so second condition means f (x) > 0 for each x > 0 .

It is well known that since f is Cauchy function, it is increasing so f (x) = cx

and substituing f (x) = x.

26. Find all functions f : R R such that f (f (x) + y ) = x + f (y ) for all

x, y R The set { x R |f (x) = x} has a ﬁnite number of elements.

Solution. [by socrates] Put y :=

Hence, f (0) =

0 to get f (f (x)) = x

+ f (0) so f is bijective.

0 , f (f (x)) = x and f (x + y ) = f (x) + f (y ).

Let g (x) = f (x) + x. Then g (x + y ) = g (x) + g (y ). If g (a ) = 0 for some a = 0

So g (x) = 0 ⇐⇒ x = 0 .( )

Then f (a ) = f (a b + b ) = f (a b ) +

Now, take a, b such that f (a )

then g (2 n a ) = 0 , n N , contradiction.

= f (b ).

f

( )

(b ) =f (a b ) = 0 =a = b. Thus, g is injective.

We have g (f (x)) = f (f (x)) + f (x) = x + f (x) = g (x) =f (x) =

x.

27. Find all functions f : R R such that for all x, y, z R :

f (f (f (x)) + f (y ) + z ) = x + f (y ) + f (f (z )).

Solution. [by socrates] Putting y, z := 0 we see that f is bijective. So f (c ) = 0

 for some c ∈ R . Putting x := 0 , y := c we get f (f (z )) = f (z + f (f (0))) so, by injectivity, f (x) = x + c and ﬁnally f (x) = x.

28. Find all functions f : R R such that

f ( x + f (x)

2

+ y + f (2 z )) = 2 x f (x) + f (y ) + 2 f (z ),

1 FUNCTIONAL EQUATIONS

14

for all x, y, z R .

Now if f (a ) = f (b ),

then P (0 , 0 , a ), P (0 , 0 , ) f ( a ) = f ( ) and then P (a, , 0), P (b, a , 0) a =

Solution. [by goldeneagle] Let P (a, b, c) be the assertion.

b

2

b

2

b

2

2

2

2

b . So f is injective. Also P (x, x, 0) gives us that f is surjective. Deﬁne f (0) = t

and f (a ) = 0.

a = 2 + f (2 a ),

P (0 , 0 , a )

t

f ( 2 + a + f (2 a )) = t f (2